Phenolic compounds of brown algae - Noora Barzkar; Svetlana Ivanova; Stanislav Sukhikh; Danil Malkov; Svetlana Noskova; Olga Babich (Elsevier Ltd., 2024)
The ocean is rich in aquatic plants (macroalgae) containing a large amount of valuable organic substances, including phenolic compounds. The aim of this study was to summarize the results of studies on the composition, structure, and extraction methods of phenolic compounds of brown algae in relation to their biological activity and prospects of application in pharmaceutics and nutriciology. Brown algae extracts were found to contain florotannins, terpenoids, mycosporine-like amino acids, thichocarpols, meroditerpenoids, colpol, coumarins, and others. This article compares methods for the extraction of phenolic compounds. Currently, all extraction methods can be divided into traditional methods (solvent extraction) and promising methods (pressurized liquid, microwave, ultrasonic, and supercritical fluid extraction). It was found that the most efficient ultrasonic extraction is characterized by high yield of extracts, scalability, short extraction time and preservation of stability of polyphenolic compounds. The highest antioxidant activity (0.36 ± 0.01 mg PGE/mL) was obtained using ultrasonic extraction. Phenolic compounds derived from brown algae are known to have a broad spectrum of biological activity. This review examines the anti-inflammatory, antioxidant, ant neurodegenerative, and other properties of phenolic compounds. Phenolic compounds are recognized as powerful antioxidants that can protect nucleic acids, proteins, and other biomolecules from oxidative stress. Phenolic compounds found in various marine algae species have been shown to have cytotoxic and antitumor properties. Literature review, indicates the high potential of using brown algae as a source of phenolic compounds for nutraceuticals and pharmacology.